Citizenship : a reality far from ideal - Kakabadse, Andrew; Kakabadse, Nada.; Kalu, Kalu Ndukwe (Basingstoke : Palgrave Macmillan, 2009)
"This unique collection of original works examines the relationship between citizen and state. Nine insightful contributions range from a transnational analysis of the corrosive influence of wealth elites on the functioning of the state, to models of state and citizen governance, to contrasting philosophies of citizenship"--Provided by publisher.
Machine generated contents note: Introduction--A.P.Kakabadse&--N.K.Kakabadse * Postmodern Citizenship: Logic and Praxis in State and Identity--K.N.Kalu * Global Governance Consideration for World Citizenship--N.Kakabadse &--A.Kakabadse * Citizenship and the Individual--A.Sementelli * Citizenship, the Public Interest and Governance--J.Dixon &--M.Hyde * When Good Citizens Say No: Bad Laws and Law-abidingness--W.D.Richardson * Reconceptualizing Citizenship and Identity: Contextual and Attitudinal Responses Towards State and Civic Obligation in the United Kingdom--N.Kakabadse, A.Kakabadse &--K.N.Kalu * The Citizen and the State: A Progressively Subversive, State Determined, and ICT Mediated Relationship--N.Kakabadse &--A.Kakabadse * Council-Manager Government at 100: Facilitative Governance and Citizenship Ethics in the Administrative State--V.Vogelsang-Coombe, L.F.Keller &--S.Murray * Does the Notion of Corporate Citizenship Make Sense?--Y.Pesqueux Introduction--A.P.Kakabadse&--N.K.Kakabadse * Postmodern Citizenship: Logic and Praxis in State and Identity--K.N.Kalu * Global Governance Consideration for World Citizenship--N.Kakabadse &--A.Kakabadse * Citizenship and the Individual--A.Sementelli * Citizenship, the Public Interest and Governance--J.Dixon &--M.Hyde * When Good Citizens Say No: Bad Laws and Law-abidingness--W.D.Richardson * Reconceptualizing Citizenship and Identity: Contextual and Attitudinal Responses Towards State and Civic Obligation in the United Kingdom--N.Kakabadse, A.Kakabadse &--K.N.Kalu * The Citizen and the State: A Progressively Subversive, State Determined, and ICT Mediated Relationship--N.Kakabadse &--A.Kakabadse * Council-Manager Government at 100: Facilitative Governance and Citizenship Ethics in the Administrative State--V.Vogelsang-Coombe, L.F.Keller &--S.Murray * Does the Notion of Corporate Citizenship Make Sense?--Y.Pesqueux .
Formerly CIP.
Includes bibliographical references and index.
Keywords: Citizenship